2017
DOI: 10.3892/br.2017.993
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of gynaecological malignancies in south western region of Pakistan: An overview of 12 years

Abstract: Abstract. Gynaecological malignancies contribute significantly to cancer burden and have a higher rate of mortality and morbidity. The aim of this retrospective study was to determine the pattern of gynaecological malignancies identified between January, 2000 and December, 2011, at the Centre for Nuclear Medicine and Radiotherapy (CENAR). At CENAR 5,072 female patients were registered with different malignancies, of which 632 cases were gynaecological malignancies. Ovarian cancer (47%) was the most common gyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 25 publications
(21 reference statements)
5
35
0
Order By: Relevance
“…4 Contrary to this was reported from Pakistan, where ovarian cancer (72.5%) was the leading gynecological cancer. 3,6 In European countries endometrial cancers were the commonest female genital cancers. 12, 13 The second commonest cancer in our study was the ovarian malignancy followed by the corpus uteri cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Contrary to this was reported from Pakistan, where ovarian cancer (72.5%) was the leading gynecological cancer. 3,6 In European countries endometrial cancers were the commonest female genital cancers. 12, 13 The second commonest cancer in our study was the ovarian malignancy followed by the corpus uteri cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of cancer cervix, ovary, and corpus uteri was 50, 48 and 48.5 years respectively, which is comparable with studies done by Agarwal et al 10 But according to SEER registry, the median age of occurrence of cervical cancer was lower (48 years) whereas ovarian and uterine cancers occurred at an older age group. 6,12 The mean age of women with insitu cancer cervix was 44 years. This correlates with the fact that premalignant changes begin early in the reproductive age group and has a long lead time before it becomes malignant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cervical cancer is the third most frequent neoplasm among women worldwide (Rocha et al, 2017). In 2017, a study showed that ovarian cancer (47%) followed by cervical cancer (29%) are the most common gynecological malignancy among Pakistan women (Manzoor et al, 2017). Despite continuous advances in cancer biology research, the etiology of ovarian and cervical cancer are not known exactly, partly because of the inconsistency of findings among epidemiological studies (Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Almost similar results (48%) were found by Manzoor H et al in a study conducted in Pakistan. 15 Though it is more common in developed countries but the incidence is quite high in our study of developing country and might be the result of new trends in lifestyle which act as contributing factors like late conception, short families and lack of breast feeding. 16 Also the dietary habits of our population have changed tremendously over the last decade and this in combination with reduced physical activity has contributed to weigh gain in our female population.…”
Section: Resultsmentioning
confidence: 71%